The Mystery of the Unknown Poem by Rustaveli - Elguja Khintibidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
The present issue of the Journal introduces a French translation of the unknown poem considered to be written by Rustaveli along with Georgian translation performed from that French original. The French translation of the poem caused a lot of controvery among Georgian scholarly circles and mass media in the 20th century.